[3+2] Annulation of Donor–Acceptor Cyclopropanes with Vinyl Azides - Kaga, Atsushi; Gandamana, Dhika Aditya; Tamura, Sayako; Demirelli, Mesut; Chiba, Shunsuke (Synlett, 2017)
A Sc(OTf)3-catalyzed reaction of vinyl azides with donor–acceptor cyclopropanes affords highly functionalized azidocyclopentanes in a diastereoselective fashion. The resulting azidocyclopentanes could be transformed into various cyclic scaffolds.
Keywords: vinyl azides; donor–acceptor cyclopropanes; cyclopentanes; [3+2] annulation; Lewis acids